Pengaruh Kepuasan Kerja, Stres Kerja, dan Burnout Terhadap Turnover Intention (Studi Pada PT. Lotus Indah Textile Industries Kabupaten Nganjuk) - KARDIAWAN, RIZA; BUDIONO, (Jurnal Ilmu Manajemen (JIM), 2018)
The main purpose of this research is to determine the impact of job satisfaction, job stress, and burnout on turnover intention. This type of research is quantitative. The sampling technique is used Slovin theory. The technique of collecting data was by distributing questionnaire for 306 respondents of PT. Lotus Indah Textile Industries. The statistical analysis used in this research by using SPSS version 23. The scale measurement in this study using a Likert scale. Conclusion of this research show that the job satisfaction has significant negative impact on turnover intention, job stress has significant positive impact on turnover intention, burnout has significant positive impact on turnover intention, furthermore job satisfaction, job stress, and burnout coincide to impact turnover intention. Keywords: Job Satisfaction, Job Stress, Burnout, Turnover Intention